Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Pembelajaran Inkuiri di Sekolah - Rosinta Rosinta; Zaiyasni Zaiyasni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
The purpose of this research is to describe the improvement of the integrated thematic learning process by using the inquiry learning model in class IV SDN 05 Percobaan Bukittinggi. This type of research is Classroom Action Research (CAR) using qualitative and quantitative approaches. The research subjects were teacher and 29 students of grade IV SDN 05 Percobaan City of Bukittinggi. The results showed the value of planning the first cycle learning 79.54% and increasing the second cycle 93.18%. The observations of aspects of the first cycle teacher 81.24% and 93.75% increased the second cycle. The results of observations of aspects of students in the first cycle were 79,68% and the second cycle increased 93.75%. Based on these results, it can be concluded that by using inquiry learning models can improve the integrated thematic learning process.